In Vivo Antimalarial Activity of Cyperus rotundus and Its Combination with Dihydroartemisinin against Plasmodium berghei - Sakaewan Ounjaijean; Charupa Lektip; Voravuth Somsak (Advances in Pharmacological and Pharmaceutical Sciences, 2024)
Background. The increase in the number of drug-resistant Plasmodium species continues to be a serious public health concern. Therefore, identification of the potential novel antimalarial drugs derived from therapeutic plants could help solve this issue. This study investigated whether Cyperus rotundus aqueous crude extract (CRE) and its combination with dihydroartemisinin (DHA) were effective against Plasmodium berghei ANKA-infected mice. Methods. CRE was prepared from C. rotundus rhizomes and evaluated using acute and subacute toxicity tests on BALB/c mice. The antimalarial effectiveness of CRE was assessed at 100, 200, and 400 mg/kg in a 4-day suppressive test with curative and prophylactic testing and measurement of packed cell volume (PCV), body weight (BW), rectal temperature, and mean survival time (MST). Results. Following acute and subacute treatment, CRE caused no harmful effects or mortality in mice. When compared with that in the untreated control, infected mice administered with 400 mg/kg of CRE in a 4-day suppressive test exhibited the strongest antimalarial activity (55.30% inhibition) with prolonged MST. However, curative and prophylactic assays did not reveal CRE to have antimalarial activity. In comparison with that achieved with the single therapy, the combination of DHA and CRE at ED50/2 (1 and 200 mg/kg, respectively) produced considerable antimalarial activity at 90.08% inhibition with synergism (combination index = 0.21701). For the other parameters, CRE administration prevented malarial-induced changes in PCV, BW, and rectal temperature. Conclusions. CRE treatment significantly inhibited malaria in the 4-day suppressive test, and CRE combined with DHA had a synergistic antimalarial effect.